The Influence of Digital Literacy and Learning Motivation on Digital Marketing Content Creation Competency in Grade X and Xi Students of Digital Business at Smks Budi Agung Medan - Yessi Novitasari Laia; Lenti Susanna Saragih (LP2M IAIN Palopo, 2026)
This study aims to determine the influence of digital literacy and learning motivation on the competence of digital marketing content creation in students in grades X and XI of the Digital Business Skills Program at SMKS Budi Agung Medan. This study uses a quantitative approach with a survey method. Data collection techniques are carried out through questionnaires, observations, and documentation. The questionnaire instrument was compiled using the Likert scale to measure digital literacy levels, learning motivation, and digital marketing content creation competencies. The population in this study is 55 students in grades X and XI of the Digital Business Skills Program. Because the population is relatively small, all members of the population are sampled using the saturated sampling technique. The results of the study show that digital literacy and learning motivation have a positive and significant influence on students' digital marketing content creation competence. These findings indicate that the better the students' ability to utilize digital technology and the higher their motivation to learn, the better their competence in producing digital marketing content. Conversely, low digital literacy and learning motivation can have an impact on declining students' ability to develop content that suits digital marketing needs. Thus, strengthening digital literacy and increasing learning motivation are important factors that need to be considered in an effort to improve the competence of digital marketing content creation in students of the Digital Business Expertise Program.